Operative treatment of athletic pubalgia in competitive athletes: a retrospective study - Koutserimpas, C.; Vlasis, K.; Makris, M. C.; Ioannidis, A.; Konstantinidis, M. K.; Antonakopoulos, F.; Athanasopoulos, P.; Mazarakis, A.; Papagelopoulos, P. J.; Konstantinidis, K. M. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Athletic pubalgia is an obscure sport injury, presenting mainly with groin pain during twisting movements. The present 15 year study reports outcomes, intraoperative findings and complications of the endoscopic surgical treatment in competitive athletes. METHODS: All competitive athletes, from 2004 to 2018, suffering from athletic pubalgia, treated with laparoscopic Total Extra-Peritoneal technique, at the Department of General, Laparoscopic, Oncologic and Robotic Surgery of the Athens Medical Center were included in this retrospective cohort. Postoperative pain, complications, return to previous training routine and patients` satisfaction were evaluated. RESULTS: A total of 130 patients (115; 88.5% males and 15; 11.5% females) with a mean age of 26.7±7.5 years were evaluated. Preoperatively, mean numeric scale pain was found to be 7.7±1.7. Three days postoperatively, the mean numeric pain scale was 3.4±1.5, showing 55.8% decrease. The mean time for return to sports activity was found to be 6.27±3.02 weeks. Regarding complications, six patients (4.6%) had slight numbness at the groin area during the first 6 postoperative months and one patient (0.8%) suffered from a postoperative hematoma. No recurrence was observed. At the final follow-up (mean 76.58±46.5 months), a total of 97 (74.7%) patients were very satisfied, 31 (23.8%) satisfied and two (1.5%) not satisfied with the outcome. CONCLUSIONS: Laparoscopic operative treatment in competitive athletes suffering from athletic pubalgia seems to offer rapid recovery, rapid return to sports, as well as very low complications rate and no recurrence.